2019
DOI: 10.5539/ies.v12n11p154
|View full text |Cite
|
Sign up to set email alerts
|

The Attitudes of Islamic Education Teachers Towards the Use of Social Media in Teaching and Learning

Abstract: The aim of this study was to identify and analyse the Islamic Education teachers’ attitudes, difficulties and purposes while using social media in the educational processes in the Saudi context. In doing so, this study adopted a quantitative, descriptive approach based on empirical data collected by means of a questionnaire. The study sample consisted of 124 teachers of Islamic Education in Hail, Kingdom of Saudi Arabia (KSA). While the participants reported positive attitudes towards the use of social media i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…For this reason, it is expected that teachers attribute meaning to social media based on their experiences in daily life rather than using them for educational purposes. According to the research results of studies by Al-Harbi (2019) and Mansour (2015), teachers used social media for personal purposes rather than teaching activities. The studies in the literature showed that, rather than for educational purposes, social media was generally used for reasons such as selfexpression; personal enjoyment and passing the time; following current agendas; conducting research; communication; sharing photos and videos; shopping; socializing; playing games; making friends and exchanging information (Acun, Yücel, Belenkuyu & Keleş, 2017;Baz, 2018;Park & Kaye, 2019;Salzman, 2019;Tejedor, Carniel-Bugs & Laque, 2019;Van Erkel & Van Aelst, 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…For this reason, it is expected that teachers attribute meaning to social media based on their experiences in daily life rather than using them for educational purposes. According to the research results of studies by Al-Harbi (2019) and Mansour (2015), teachers used social media for personal purposes rather than teaching activities. The studies in the literature showed that, rather than for educational purposes, social media was generally used for reasons such as selfexpression; personal enjoyment and passing the time; following current agendas; conducting research; communication; sharing photos and videos; shopping; socializing; playing games; making friends and exchanging information (Acun, Yücel, Belenkuyu & Keleş, 2017;Baz, 2018;Park & Kaye, 2019;Salzman, 2019;Tejedor, Carniel-Bugs & Laque, 2019;Van Erkel & Van Aelst, 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Based on the initial mapping regarding articles included in the inclusion criteria, it can be identified that research trends on sustainable Islamic education in 2019 focus on the use of social media in learning Islamic education (Al-Harbi, 2019) . Through social media, Islamic education teachers can provide useful educational content, enable teachers to share educational resources, conduct virtual classes, and provide easy access to relevant Islamic values.…”
Section: Continuing Islamic Education In Realizing Quality Education ...mentioning
confidence: 99%
“…Digital tools, virtual model, classroom teaching, science practical activities, can be obtained through the help of different visual tools. Among all learning of people, about 90% of learning is contributed by visual perception whereas the way of 8% and 2% of information to brain is ears and other sense organs, respectively (Karki, 2020). Existing situation of Information & Communication Technology (ICT) Development in Nepal, reported by (Sharma & Kim, 2016), Nepal is ranked 165th with a score of 0.234 in the e-government development index (United Nations, 2014).…”
Section: Introductionmentioning
confidence: 99%